Intraobserver and interobserver reproducibility of the old and new classifications of toracolombar fractures() - Lopes, Felipe Augusto Rozales (Rev Bras Ortop, 2018)
OBJECTIVE: To evaluate the inter and intraobserver agreement of the Magerl AO and AOSpine thoracolumbar fracture classification systems. METHODS: The participants were divided into two groups, the first composed of six spinal surgeons and the other composed of 18 medical orthopedic residents. On two different occasions, separated by an interval of one month, the participants analyzed and classified 25 radiographs with thoracolumbar fractures using both thoracolumbar fracture classification systems, Magerl AO and AOSpine. The results were analyzed for classification reliability using the Kappa coefficient (k). RESULTS: The Magerl AO classification system showed a fair interobserver agreement (k = 0.32), considering the fractures type and subtype, whereas the AOSpine classification system showed a moderate interobserver agreement (k = 0.59). The Magerl AO classification showed a fair intraobserver agreement for both residents and specialists (k = 0.21 and 0.38, respectively), while the AOSpine showed a substantial agreement between residents (k = 0.62) and moderate between specialists (k = 0.53). CONCLUSIONS: When evaluating fracture morphology, the AOSpine thoracolumbar fracture classification system presented a better reliability and reproducibility compared to the Magerl AO classification system.